Complications after open and robot‐assisted radical prostatectomy and association with postoperative opioid use: an analysis of data from the PREVENTER trial. (17th August 2020) - Huang, Mitchell M.; Su, Zhuo T.; Becker, Russell E.N.; Pavlovich, Christian P.; Partin, Alan W.; Allaf, Mohamad E.; Patel, Hiten D.
Abstract : Objective: To evaluate perioperative complications for open radical prostatectomy (ORP) and robot‐assisted RP (RARP) for patients enrolled in the PREvention of VENous ThromboEmbolism Following Radical Prostatectomy (PREVENTER; ClinicalTrials.gov Identifier: NCT03006562) trial, to determine predictors and impact on opioid consumption. Patients and Methods: A prospective cohort of 500 patients undergoing ORP and RARP was followed to determine rates of complications and opioid use. Complications were classified 30 days after RP using the Clavien–Dindo system. Patient characteristics and outcomes were compared using appropriate statistical tests. Logistic and linear regressions were performed to identify predictors of complications and evaluate the relationship between complications and postoperative opioid use. Results: A total of 124 (24.8%) men underwent ORP and 376 (75.2%) RARP, with 418 (83.6%) receiving pelvic lymph node dissection (PLND). While 83 patients (16.6%) had complications, only 19 (3.8%) were major (Clavien–Dindo Grade ≥III), with no differences by surgical approach. PLND (odds ratio [OR] 2.96, 95% confidence interval [CI] 1.25–8.71; P = 0.03) and Stage pT3b (OR 2.76, 95% CI 1.23–6.00; P = 0.01) were the only predictors of complications after controlling for potential confounders. Patients who had complications had greater inpatient ( P = 0.02) and outpatient ( P = 0.005) opioid use, which persisted after controlling for patient‐reported pain, attending surgeon variation, surgical approach, and undergoing PLND (inpatient β:77.2, 95% CI 17.9–136.5, P = 0.03; and outpatient β:21.9, 95% CI 4.7–39.1, P = 0.01). Conclusion: In an analysis of prospectively collected data, overall and major complications rates did not differ by surgical approach. Patients receiving PLND and with Stage pT3b disease had more complications. Complications were independently associated with higher inpatient and outpatient postoperative opioid use.